PUBLICATIONS OF THE WEEK. (Bookseller, 2004)
This article presents information related to new publications of the week published in the September 2004, issue of "The Bestseller." Information is compiled by Nielsen Book Data and it covers subject arrears ranging from agriculture, archaeology, ceramics and biographies. Few of the listed publications are: "Finfish and Shellfish Bacteriology Manual," "Ceramic Art in Finland: A Contemporary tradition," "Roy Jenkins: A Retrospective," "Fighting Talk: Biography of John Prescott," and "Confessions of Poacher."